The lamprey habenula provides an extreme example for the temporal regulation of asymmetric development - Guichard, Lucile; Lagadec, Ronan; Michel, Léo; Mayeur, Hélène; Fuentès, Michaël; Pain, Jordan; Heier, Noah; Rougemont, Quentin; Rodicio, Maria Celina; Barreiro-Iglesias, Antón; Blader, Patrick; Schubert, Michael; et al. (Frontiers in Cell and Developmental Biology, 2025)
By their phylogenetic position and their marked epithalamic asymmetries, lampreys are relevant models for understanding the formation and evolution of this trait across vertebrates. In this study, we use a transcriptomic approach to identify novel signature markers to characterize the highly asymmetric, bipartite organization of habenulae in lampreys. Lamprey habenulae are subdivided into two complementary subdomains related, respectively, to the lateral/ventral and the medial/dorsal habenulae of jawed vertebrates: a dorsal, right-restricted subdomain and a bilateral subdomain that includes the left habenula as well as its ventral right counterpart. Analysis of the formation of the lamprey habenula at prolarval and larval stages using a combination of morphological, immunohistochemical, and in situ hybridization approaches highlights a marked asymmetric temporal regulation. The dorsal right subdomain forms and already expresses all identified signature markers in prolarval stages. In contrast, the left and ventral right subdomain appears significantly later, with the first indication of neuronal identity elaboration in these territories being observed in larval stages. As in gnathostomes, Wnt signaling may be involved in the regulation of this unique, asymmetric mode of development, since β-catenin shows asymmetric and highly dynamic nuclear distributions both in neural progenitors and differentiated neuronal precursors of the two habenular subdomains. These data confirm the importance of lampreys to unravel the developmental logic underlying the recurrence and variation of habenular asymmetries in vertebrates and pave the way for future functional analyses.